Sample handling concept for in-situ lunar regolith analysis by laser-based mass spectrometry - Keresztes Schmidt, Peter; Hayoz, Sébastien; Piazza, Daniele; Bandy, Timothy; Mändli, Patrik; Blaukovitsch, Matthias; Althaus, Michael; Plet, Benoît Gabriel; Riedo, Sven; Studer, Simon; Studer, Olivier; Bieri, Michael; et al. (2024 IEEE Aerospace Conference, 2024)
We present the current progress in developing a reflectron-type time-of-flight laser ablation ionization mass spectrometer (RTOF-LIMS) to allow for direct sensitive microanalysis of lunar regolith grains in situ on the lunar surface. The LIMS system will operate in the lunar south pole region on a CLPS mission within NASA’s Artemis program.The concept for the regolith sample handling system, which is based on a carousel disk system with a cavity to hold the sample material, will be discussed in detail. Rotating the disk takes care of transporting the sample material from the sample inlet, into which a sample delivery system of the CLPS platform deposits the regolith, to the analysis position below the mass analyzer entrance and, subsequently, disposing the material after analysis is completed. Sample preparation is achieved by passive brushes and a shaping tool to create a sample surface with the necessary planarity. Accurate control of these parameters is important to ensure consistent laser ablation conditions during sample analysis and thus reproducible chemical composition determination of the sample material. The new sample handling system design has an improved acceptance range for larger regolith grain sizes up to ~ 1 mm Ø. This in turn reduces a possible sampling bias and should lead to a more representative analysis of the regolith’s chemical composition. Sample disposal is realized by another set of brushes to clean out the cavity and to allow for new sample material to be deposited.To verify the feasibility of the sample handling concept and guiding the development thereof, laboratory experiments on a lunar regolith simulant were conducted using a prototype LIMS system. This prototype system has capabilities representative of the flight instrument currently in development regarding the mass analyzer and optical sub-system. The laboratory and flight optical sub-system is based on a microchip Nd:YAG laser system (~ 1.5 ns pulse width, λ = 532 nm, 100 Hz laser pulse repetition rate, laser irradiance ~ 1 ...